Predictors of antenatal care services utilization by pregnant women in a selected Akwa Ibom state community, Nigeria - Effiong, Ben Victor; Adhowhoarie, Oboma Lawrence (American Journal of Social Sciences and Humanities, 2023)
In Nigeria, the burden and incidence rate of maternal mortality significantly affects the achievement of the Sustainable Development Goal 3. The study was designed to investigate the factors and trends of Antenatal Care Services Utilization by Pregnant Women in Anua Community Akwa Ibom State, Nigeria. The assumptions of Andersen Behavioural Model of Health Services and Antonovsky Theory of Social Class were adopted to explain the use of antenatal care services. A combined survey was conducted to obtain primary data from 264 women between the ages of 15 and 49 selected as respondents through snowball and respondents driven sampling techniques; antenatal registers and documents at the Antenatal Care Unit of health facility were reviewed to obtain secondary data. Findings from the study showed an extended predictors of antenatal care services utilization rooted in the socio-cultural, economic, demographic and environmental configurations of the study area. Based on the findings, strengthening of health facility, the implementation of health intrventions and enforcement of policies such as free enrolment of all pregnancies and compulsory Antenatal Care Services Utilization in the study area were recommended. The recommendations have inplications to reduce the incidence rate of maternal mortality and improve child health outcomes in the study area.